Pertanggungjawaban Pidana Terhadap Pelanggaran Standar Operasional Prosedur Pada Proses Penangkapan - fathanah, Putri; Sukmareni; Fitri Z, Yenny (IAIN Langsa, 2023)
In carrying out the task of arresting the existence of standard operating procedures, with the existence of standard operating procedures, it can build a methodical, deliberate, measurable, and representable framework according to the legal basis that guides it. In its implementation, there are many violations regarding standard operating procedures. One example is in the case of arrests that do not meet the standard procedures, and if the standard operating procedures are violated, then of course there is accountability that must be carried out. The results of this study aim to determine what forms of violations of standard operating procedures result in death in the arrest process and liability for violations of standard operating procedures that result in death in the arrest process by the police based on the study of decision number 91/Pid.B/2021/PN.Koto baru. The method used is normative jurisprudence, which is legal research aimed at written regulations. This regulation is closely related to the library because it requires secondary material from the library. Based on the results of the research, it can be concluded that the defendant did not comply with the procedures in accordance with what has been regulated in the law and Perkapolri. And in terms of criminal responsibility regarding the verdict handed down by the judge to the defendant, it is in accordance with Article 354 paragraphs (1) and (2) of the Criminal Code on serious maltreatment charged to the defendant and in accordance with the applicable elements.